Christian Michael Wolff (1707–1789) and his Chorale Preludes for Organ. Issue 2 (3rd July 2019) - Talbot, Michael
Abstract : An organist by training and occupation, Christian Michael Wolff lived most of his life in the small Pomeranian town of Stettin (today, Szczecin in Poland), but a period spent in Berlin between 1728 and 1732 widened his horizons and brought his activity as a composer within the orbit of the so-called Berlin school, representative figures of which included the Graun brothers, J.J. Quantz and C.P.E. Bach. Four early orchestral works dating from the years around 1740 reveal Wolff's skill and originality as a composer, displaying some attractive stylistic features that continued to characterize his music after his transition to a more empfindsam musical language in the 1760s. In the 1770s Wolff began—belatedly—to publish collections of his works. His accompanied sonatas (1776) and songs for voice and written-out keyboard accompaniment (1777) have received comment from modern scholars, who are struck and sometimes bemused by the music's bold juxtaposition of conservative (Baroque, contrapuntal, structured) and progressive (Classical, homophonic, improvisatory) elements. Similar contrasts pervade the fifty-seven chorale preludes for organ making up Wolff's final and most impressive publication (1782), which has been less kindly treated by modern commentators, resistant to his mixture within a single movement of features associated with different varieties of chorale prelude and unsympathetic towards his penchant for decorative chromaticism. The analysis and evaluation of that collection is the main business of this article, which seeks to pave the way for the wider appreciation and performance of Wolff's highly individual music.